A Programmable Dual‐Regime Spray for Large‐Scale and Custom‐Designed Electronic Textiles (Adv. Mater. 9/2022). Issue 9 (3rd March 2022) - Chang, Taehoo; Akin, Semih; Kim, Min Ku; Murray, Laura; Kim, Bongjoong; Cho, Seungse; Huh, Sena; Teke, Sengul; Couetil, Laurent; Jun, Martin Byung‐Guk; Lee, Chi Hwan
Abstract : E‐Textiles In article number 2108021, Laurent Couetil, Martin Byung‐Guk Jun, Chi Hwan Lee, and co‐workers report how direct spray writing of functional nanomaterials into stretchy fabrics is enabled at sub‐millimeter resolution to produce e‐textiles with custom designs. The e‐textiles fit well various body sizes and shapes of large animals under ambulatory conditions, allowing for high fidelity monitoring of health conditions from a distance.